2019
DOI: 10.1111/jtxs.12410
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐reported ease of eating foods of different textures in young children with Down syndrome

Abstract: Food texture has been identified as a significant contributor to feeding problems in children, particularly in children with Down syndrome (DS). This study examined the open‐ended survey responses of parents describing which food textures were “easy” or “difficult” for their child with DS. The open‐ended responses from the parents about textures and foods they considered “easy” or “difficult” for their child (n = 157) were coded into 26 texture categories. Chewy and firm were more frequently listed as “difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 37 publications
(62 reference statements)
1
32
1
Order By: Relevance
“…In the oral phase, immature chewing pattern and poor bolus control are common concerns. In children 1-4 years of age, common difficulties are chewy, firm and gummy/rubbery food texture, whereas creamy, soft and puree texture are often reported to be accepted (31). However, with increased age, also crispy, dry and hard food texture were more likely to be managed by the child (31).…”
Section: Feeding and Swallowing Problemsmentioning
confidence: 99%
“…In the oral phase, immature chewing pattern and poor bolus control are common concerns. In children 1-4 years of age, common difficulties are chewy, firm and gummy/rubbery food texture, whereas creamy, soft and puree texture are often reported to be accepted (31). However, with increased age, also crispy, dry and hard food texture were more likely to be managed by the child (31).…”
Section: Feeding and Swallowing Problemsmentioning
confidence: 99%
“…The 16 products were selected based on their representation of the texture spectrum (n = 15 textures). From our previous work (Ross et al, 2019), we were particularly interested in exploring the range of textures that were considered "difficult" by parents of CWDS (including firm and hard) and textures cited more frequently as "easy" textures included crispy, dissolvable, and smooth. These textures were represented along PC1 of the texture PCA.…”
Section: Final Selection Of Food Productsmentioning
confidence: 99%
“…Many parents have similarly identified texture as a main contributor to their child's feeding difficulty (Russell & Worsley, 2013;Werthmann et al, 2015), particularly among children diagnosed with Down syndrome (DS; Ross, Bernhard, & Smith-Simpson, 2019). DS is the most common chromosomal condition of babies in the United States, with approximately 6,000 babies born in the United States annually being diagnosed with DS (CDC, 2019;Mai et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed the reluctance of children (4–5 years old) with DS to chew food, instead displaying a preference to suck on an item until swallowed (Anil et al, 2019; Gisel, Lange, & Niman, 1984a; Gisel, Lange, & Niman, 1984b). In a survey of parents of children (1–4 years) with Down syndrome ( n = 157), chewy and firm were more frequently listed as “difficult” textures by parents (Ross, Bernhard, & Smith‐Simpson, 2019). Textures found to be cited more frequently as “easy” textures included creamy , crispy/crunchy , dissolvable , mushy , puree , smooth , and soft .…”
Section: Introductionmentioning
confidence: 99%